Bimbingan Belajar Akuntansi Sederhana Bagi Entrepreneur Umkm Kopi Berbasis SAK EMKM - Faizal David Julio; Dian Ruhamak; Andy Chandra Pramana; Nonni Yap Yap (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
For owners of Micro Small and Medium Enterprises (MSMEs), financial recording and reporting is certainly the main issue. SAK EMKM stands for The Financial Accounting Standard of Small and Medium Micro Entities formulated by the Indonesian Accountants Association (IAI). This standard is aimed at businesses that have not been able to meet the accounting standards of Entities Without Public Accounting (ETAP). MSMEs are expected to be able to apply SAK ETAP as a reference in the creation of their financial records and statements. Omah Kopi Mandiri is one of the MSMEs that have not implemented SAK ETAP. This PkM result is the increasing insight of MSME actors, especially Omah Kopi Mandiri and prospective millennial entrepreneurs in the Omah Kopi Mandiri environmental area to SAK ETAP and the science of accounting recording and reporting, so as to increase their quality into superior and competent resources.